Frameworks of IT prosumption for business development 2026-02-16T04:46:15+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Pankowska, Magorzata (Advances in business information systems and analytics book series, 2014)

(untitled)
"This book investigates the latest empirical research on active use of information technology resources, enabling users with new methodologies, tools, and opportunities to impact application development processes"--Provided by publisher